Pengaruh Asimetri Informasi Pada Kebijakan Dividen Dengan Investment Opportunity Set Sebagai Variabel Pemoderasi - Linda Yasmita, Ni Putu; Widanaputra, Anak Agung Gde Putu (E-Jurnal Akuntansi; Vol 22 No 3 (2018), 2018)
The purpose of this study is to obtain empirical evidence of investment opportunity capability sets to moderate the influence of information asymmetry on dividend policy. This research was conducted at a manufacturing company listed on Indonesia Stock Exchange 2014-2016. Sampling method used is purposive sampling. The sample size is 30 with 72 observations. Technique Data analysis used is test of Moderated Regression Analysis (MRA). Based on the results of the analysis, it is known that the investment opportunity set is not as a moderator of the influence of information asymmetry on the dividend policy. This suggests that when firms have high investment opportunities with high levels of asymmetry, it is not necessarily that the company will pay low dividends or not share them to the shareholders, since management will manage earnings annually as reserves to be reinvested without reducing the proportion of dividend payout to investors. This study provides implications for investors as a consideration in investing in a company to see how the bid ask and dividend payout ratio of the company's shares. Keywords : Asymmetry of information, investment opportunity set, dividend policy